Research on the effectiveness on implementing direct selling technique for MLM product in Kuching area. A case study of: Amway (Malaysia) Sdn Bhd / Sharifah Maziah Wan Habib - Wan Habib, Sharifah Maziah (2008)
The direct selling industry has grown rapidly over recent years. Changing lifestyles, demographics and economic recession have all been factors influencing this growth. It provides people with business opportunities across the globe. Direct selling is not about ‘getting rich quick’; it is about creating rewards for effort and initiative. With low risk and low capital investment, Direct Selling Company provides people with the opportunity to achieve and to improve their lives. As a leading player in the world of direct selling, it is helping to ‘clean up’ the industry and provide a valuable and acceptable form of product distribution. In an impersonal fast-moving world driven by technology, direct selling provides the personal touch. All direct selling should be legal, decent, honest and truthful. Every direct selling activity should be carried out with a due sense of social responsibility. No direct selling should be carried out as such, to impair confidence in direct selling. All direct selling activities should conform to the principles of fair competition as generally accepted in business, in particular with regard to the terms of the offer, including the price and modes of payment, and the methods and form of the contact with the consumer, the methods of presentation and demonstration of, and the information on the product, the fulfillment of any obligation arising from the offer or any operation, including delivery and connected with it.